Isim Maushul dan Maknanya dalam Surah An-Nur (Suatu Analisis Bahasa (Ilmu Nahwu)) - hamisa, hamisa; Hamsa, Hamsa; Fauziah, St. (Al-Syamail: Jurnal Bahasa dan Sastra Arab, 2024)
This research is qualitative research descriptive. This means that this research examines and describes the noun maushul and its meaning in Surah an-Nur (an analysis of language (Nahwu science). A language analysis especially regarding name maushul, position/i’rob and its meaning. The approach used by researchers is the Nahwu science approach by analyzing the problems to be studied. The data collection technique is carried out through literature review by searching library research data to obtain scientific information collected through literature review as a reference for problems deemed appropriate, namely by searching for data related to the researcher’s title. In analyzing the data, researchers used descriptive qualitative methods (Library Research). The research results of Surah an-Nur show that 64 verses in Surah an-Nur. In it there are 62 isim maushul, of which 30name maushul nash/mukhtas and 32 isim maushul musytarik. and there are 3 forms of isim maushul nash/mukhtash in surah an-Nur, namely اَلَّذِي as form مُفْرَدٌ مُذَكَّرٌ dan اَلَّذِيْنَ as a form off جَمْعُ مٌذَكَّرٍ سَالِمْ and the third form namely الّٰتِيْ as a form off جَمْعُ مُؤَنَّثٍ سَالِمٌ and the form off isim maushul musytarik is available ما and .من There are several meanings of isim maushul contained in the Al-Qur’an surah an-Nur. The first is the prohibition against accusing a good woman of adultery before bringing in a reliable witness, the second is etiquette when visiting, the third is the command for women to cover their entire body except the palms of their hands and face and maintain their purity, the fourth is freeing their servants, and the last is proof of signs. the greatness of Allah SWT. there are several forms of i’rob isim maushul in surah an-Nur consisting of rafa’ nashab, and jar. In the rafa’ position, maushul nouns become mubtada, mubtada’ muakhar, fail, naibul fail, na’tun and man’ut. As for the nashab position of isim maushul mustasna, isim inna and na’tun. And the last position of jar, the noun maushul in surah an-Nur becomes the position of jar when it starts with the letter jar (jar biharfi) and mudhafun ilaihi.